Implementasi Karakter, Kurikulum ANALISIS IMPLEMENTASI KARAKTER DIMENSI BERGOTONG ROYONG PADA TEMA GAYA HIDUP BERKELANJUTAN SISWA MI MUHAMMMADIYAH 09 KARANGWUNGULOR: IMPLEMENTASI KARAKTER BERGOTONG ROYONG - Faizal Dzulqornain Afandi Nur; Rizka Novi Irmaningrum; Arfian Mudayan (Jurnal Tematik, 2026)
This study aims to determine the implementation of the character dimension of mutual cooperation on the theme of a sustainable lifestyle for students of MI Muhammadiyah 09 Karangwungulor. This study uses a descriptive qualitative approach. The subjects in this study were all teachers and students of MI Muhammadiyah 09 Karangwungulor. Using data collection techniques, namely observation, interviews, and documentation studies. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. This study uses data validity, namely source triangulation and technique triangulation. This study aims to determine how the implementation of the character dimension of mutual cooperation on the theme of a sustainable lifestyle for students of MI Muhammadiyah 09 Karangwungulor. The results of this study are that the implementation of the character of the mutual cooperation dimension on the theme of sustainable lifestyle of students of MI Muhammadiyah 09 Karangwungulor is as follows: 1) The mutual cooperation dimension has three aspects, namely the collaboration aspect, the caring aspect and the sharing aspect. The collaboration aspect at MI Muhammadiyah 09 Karangwungulor has often been seen in students. The caring aspect has also been seen and the sharing aspect is less seen in students. 2) there are three supporting factors for students to have an interest in cooperation in group work, students have implemented a sustainable lifestyle such as processing used goods into crafts. the compactness of the guardians of students in supporting student activities at school. 3) there are two obstacles, the limited number of students and there are some students who are not good at interacting.